2012
DOI: 10.3310/hta16240
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cystic fibrosis-related diabetes: a systematic review.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 182 publications
1
39
0
2
Order By: Relevance
“…Screening for CFRD is important as highlighted by a recent systematic review [14]. The use of HbA1c to diagnose type 1 and 2 diabetes has recently been introduced (≥ 6.5% (48 mmol/mol) = diabetes) by the American Diabetic Association [18] and so translating this to CFRD may be logical although this is heavily debated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for CFRD is important as highlighted by a recent systematic review [14]. The use of HbA1c to diagnose type 1 and 2 diabetes has recently been introduced (≥ 6.5% (48 mmol/mol) = diabetes) by the American Diabetic Association [18] and so translating this to CFRD may be logical although this is heavily debated.…”
Section: Discussionmentioning
confidence: 99%
“…Receiver operating curves (ROC) were constructed to determine the optimal threshold for the selected criteria. As no recommendations exist for acceptable test screening sensitivity and specificity for CFRD, our aim was to produce a diabetes screening tool with excellent sensitivity (N 95% -to minimise the risk of missing a patient with a positive OGTT) and acceptable specificity (to reduce the need for a routine OGTT as much as possible) as it is well recognised that a higher sensitivity can usually only be achieved at the cost of poorer specificity [14]. From the final screening criteria, we explored the relationship of the measured clinical characteristics and the probability of a positive screen outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Genetically determined function of the remaining b-cells and insulin resistance associated with infection and inflammation may also play a role. Encouraging data suggest that improved screening (544,545) and aggressive insulin therapy have narrowed the gap in mortality between cystic fibrosis patients with and without diabetes, and have eliminated the sex difference in mortality (546). Recent trials comparing insulin with oral repaglinide showed no significant difference between the groups.…”
Section: Drugs Contraindicated In Pregnancymentioning
confidence: 99%
“…Частота развития сахарного диабета у пациентов, страдающих МВ, увеличивается с возрастом (более 50% больных старше 40 лет) [14]. Гипергликемия способствует бактериальной колонизации легких, усугубляя нарушения функции респираторной системы, увеличивая риск развития неблагоприятного исхода [15]. С целью своевременного выявления сахарного диабета проводят ежегодный скрининг толерантности к глюкозе среди пациентов с МВ с 10-летнего возраста [16].…”
Section: Review Articles and Lecturesunclassified
“…Таким образом, восстановление нормальных значений ИМТ (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)9 ОБЗОРНЫЕ СТАТЬИ И ЛЕКЦИИ…”
Section: тяжелое течение муковисцидоза и трансплантация легкихunclassified